Protection against homologous but not heterologous challenge induced by inactivated feline immunodeficiency virus vaccines. - Hosie, M J (1995)
Whole inactivated virus vaccines from the FL4 cell line protected against challenge with homologous feline immunodeficiency virus (Petaluma strain) but not against a heterologous FIV isolate (GL-8) which is distinct from the Petaluma strain in virus neutralization. Protection was associated with a type-specific neutralizing antibody response and was retained when the challenge virus was propagated in an unrelated cell line.